Physicochemical Quality and Fatty Acid Profile in the Meat of Goats Fed Forage Cactus as a Substitute for Tifton 85 Hay - Pinheiro, Rafael S. B. [UNESP]; Farias, Iasmin M. S. C. [UNESP]; Francisco, Caroline L. [UNESP]; Moreno, Greicy M. B. (MDPI, 2023)
Low rainfall in Northeast Brazil is a limiting factor for animal production. Forages that present crassulacean acid metabolism, such as forage cactus, are adapted to the edaphoclimatic conditions of this region, as they lose little water through the stomata. Thus, the objective was to evaluate the physical and chemical quality, fatty acid profile and sensory acceptance of the meat from goats fed forage cactus as a substitute for Tifton 85 hay. Twenty-one uncastrated mixed-breed goats with a mean body weight of 18 ± 0.86 kg and 7 ± 1 months of age were used. A completely randomized design with three treatments and seven replications per treatment was performed. The inclusion of 0 (control), 25 and 55% of forage cactus in substitution of Tifton 85 hay in the diet of the goats was evaluated. The lipid content in the meat of animals fed 25 and 55% of forage cactus was 1.33% and 1.26%, respectively, and was lower (p < 0.05) in relation to the meat of animals that received the control diet (1.56%). The inclusion of 55% of forage cactus provided an increase (p < 0.05) in the content of monounsaturated fatty acids in the meat (52.71%) in relation to the control meat (37.75%). Sensory analysis differed (p < 0.05) between treatments. We recommend replacing Tifton 85 hay with 55% forage cactus, as it presents greater sensory acceptance, and provides lower lipid content and higher content of monounsaturated fatty acids in goat meat.
Keywords: cladodes; climate changes; healthy meat; ruminant; sustainability